First you simply have to substitute 2 in replace of all the a's, and -2 in replace of all of the b's
4((2)2+2(-2))
Then you want to follow the order of operations, PEMDAS (Parantheses-Exponent-Multiplication-Division-Addition-Subtraction), and multiply within the parantheses.
4(4+(-4))
Next you will add within the parantheses (So add the 4 and -4 together)
4(0)
Lastly multiply
0
Your answer is 0
Hope this helps!
Answer:B
Step-by-step explanation:
Honestly when I did the math I got closest to b so I think it's B hope his helps
Answer:
it will be 8xy
Step-by-step explanation:
2x+6y=-6
2x+6y=8xy
Answer: x = -1
Step-by-step explanation:
- 2x-3= - 4x+9
- 2x+4x = -9 + 3
- 6x = -9 + 3
- 6x/6 = -6/6
- x = -1